Students’ Perceptions on the Effectiveness of the Taboo Game in Enhancing English Vocabulary Acquisition - Lestari, Sri Dewi; Damanik, Emeliya Sukma Dara (Universitas Lancang Kuning, 2024)
The integration of game-based learning methods in language education has been explored to varying extents, yet there remains a significant gap in understanding how specific games like the Taboo Game can impact English vocabulary acquisition among junior high school students. This study aims to address this gap by examining students' perceptions of using Taboo to enhance their English vocabulary. Participants included 34 junior high school students from MTs Madrisatul Ikbar during the first semester of the 2023/2024 academic year, with a subset of 12 students selected for interviews. A purposive sampling technique was employed to identify participants. The study utilized a descriptive method with a qualitative approach, collecting data through observation sheets, questionnaires, and interviews. Findings indicate that the majority of students perceived the Taboo Game positively, noting improvements in vocabulary retention, increased engagement, and reduced anxiety in learning English. Despite some differing opinions, the overall consensus highlighted the game's effectiveness and enjoyment as a learning tool. This study underscores the potential of Taboo as an engaging and effective method for enhancing English vocabulary skills in a junior high school setting.